Основні тренди в законодавчому регулюванні лобіювання у країнах Західної Європи - Нестерович, В.; Nesterovych, V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто основні тренди в законодавчому регулюванні лобіювання у країнах Західної Європи на прикладі чотирьох країн – Німеччини, Франції, Великої Британії та Ірландії. Автором виокремлюється важлива роль інституцій Європейського Союзу у рамках реалізації ними антикорупційних ініціатив щодо вдосконалення лобістського законодавства у його державах-членах. Звертається увага на доповнення законодавчого регулювання лобіювання ефективною системою його саморегулювання за рахунок розроблення лобістськими спілками корпоративних морально-етичних актів професійної поведінки. The article considers basic trends in legislative regulation of lobbying in Western Europe on the example of four countries - Germany, France, Great Britain and Ireland. The author singled out the important role of EU institutions in the framework of their anti-corruption initiatives to improve its lobbying legislation in the states – members of the Union. The basic trends in the legislative regulation of lobbying in Western Europe are: increasing transparency and openness in decision-making by public organizations authorities in the framework of anti-corruption initiatives of the European Union; availability of extraordinary demand for the possibility to represent and protect their interests in lobbying manner among commercial institutions; significant improvement of the rules of registration of lobbyists and procedure of lobbying; an effective system of declaration of the government member’s gifts or other material compensation he received during his time in office; the use of the Internet while filling in the lobbying registration forms and reports and public access to this information; supplying the legislative regulations with effective system of corporate ethical acts of
Basic Trends in Legislative Regulation of Lobbying in Western Europe
Keywords: тренди; законодавче регулювання; лобіювання; морально-етичні акти; країни Західної Європи; trends; legislative regulation; lobbying; ethical acts; Western European countries